A novel human stem cell model for Coffin-Siris syndrome-like syndrome reveals the importance of SOX11 dosage for neuronal differentiation and survival - Turan, Sören; Börstler, Tom; Kavyanifar, Atria; Loskarn, Sandra; Reis, André; Winner, Beate; Lie, Dieter Chichung (Human Molecular Genetics, 2019)
The SOXC transcription factors Sox4, Sox11 and Sox12, are critical neurodevelopmental regulators that are thought to function in a highly redundant fashion. Surprisingly, heterozygous missense mutations or deletions of SOX11 were recently detected in patients with Coffin-Siris syndrome-like syndrome (CSSLS), a neurodevelopmental disorder associated with intellectual disability, demonstrating that in humans SOX11 haploinsufficiency cannot be compensated and raising the question of the function of SOX11 in human neurodevelopment. Here, we describe the generation of SOX11(+/-) heterozygous human embryonic stem cell (hESC) lines by CRISPR/Cas9 genome engineering. SOX11 haploinsufficiency impaired the generation of neurons and resulted in a proliferation/differentiation imbalance of neural precursor cells and enhanced neuronal cell death. Using the SOX11(+/-) hESC model we provide for the first time experimental evidence that SOX11 haploinsufficiency is sufficient to impair key processes of human neurodevelopment, giving a first insight into the pathophysiology of CSSLS and SOX11 function in human neurodevelopment.
CRIS-Team WoS Importer:2019-11-12